Progression of cerebral infarction before and after thrombectomy is modified by prehospital pathways. (13th May 2021) - Kollikowski, Alexander M; Cattus, Franziska; Haag, Julia; Feick, Jörn; März, Alexander G; Weidner, Franziska; Schuhmann, Michael K; Müllges, Wolfgang; Stoll, Guido; Pham, Mirko; Strinitz, Marc
Abstract : Background: Evidence of the consequences of different prehospital pathways before mechanical thrombectomy (MT) in large vessel occlusion stroke is inconclusive. The aim of this study was to investigate the infarct extent and progression before and after MT in directly admitted (mothership) versus transferred (drip and ship) patients using the Alberta Stroke Program Early CT Score (ASPECTS). Methods: ASPECTS of 535 consecutive large vessel occlusion stroke patients eligible for MT between 2015 to 2019 were retrospectively analyzed for differences in the extent of baseline, post-referral, and post-recanalization infarction between the mothership and drip and ship pathways. Time intervals and transport distances of both pathways were analyzed. Multiple linear regression was used to examine the association between infarct progression (baseline to post-recanalization ASPECTS decline), patient characteristics, and logistic key figures. Results: ASPECTS declined during transfer (9 (8–10) vs 7 (6-9), p<0.0001), resulting in lower ASPECTS at stroke center presentation (mothership 9 (7–10) vs drip and ship 7 (6–9), p<0.0001) and on follow-up imaging (mothership 7 (4–8) vs drip and ship 6 (3–7), p=0.001) compared with mothership patients. Infarct progression was significantly higher in transferred patients (points lost, mothership 2 (0–3) vs drip and ship 3 (2–6), p < 0.0001). After multivariable adjustment, only interfacility transfer, preinterventional clinical stroke severity, the degree of angiographic recanalization, and the duration of the thrombectomy procedure remained predictors of infarct progression ( R 2 =0.209, p < 0.0001). Conclusions: Infarct progression and postinterventional infarct extent, as assessed by ASPECTS, varied between the drip and ship and mothership pathway, leading to more pronounced infarction in transferred patients. ASPECTS may serve as a radiological measure to monitor the benefit or harm of different prehospital pathways for MT.